Analisis Superposisi Gelombang Menggunakan Transformasi Fourier Diskrit - Fajar Ilham; Yani Ramdani; Gani Gunawan (Jurnal Riset Matematika, 2025)
Abstract. This study examines the use of the Discrete Fourier Transform (DFT) in analyzing wave superposition phenomena through a spectral approach. By utilizing the DFT, complex signals resulting from the overlap of periodic and non-periodic waves are decomposed into their constituent frequency components. The transformation process from the time domain to the frequency domain allows the extraction of critical parameters such as amplitude, dominant frequency, and phase shift for each individual wave. This analysis emphasizes the ability of the DFT to map the signal energy distribution and identify patterns of interfrequency interactions that are not observed in the time domain. Through numerical simulations, the accuracy of the signal reconstruction based on spectral components is evaluated by considering factors such as frequency resolution and aliasing effects. The verification results indicate that the DFT provides a reliable framework for understanding the dynamics of wave superposition, especially in the context of real time. Abstrak. Penelitian ini mengkaji pemanfaatan Transformasi Fourier Diskrit (DFT) dalam menganalisis fenomena superposisi gelombang melalui pendekatan spektral. Dengan memanfaatkan DFT, sinyal kompleks yang dihasilkan dari tumpang tindih gelombang periodik maupun non-periodik didekomposisi ke dalam komponen frekuensi penyusunnya. Proses transformasi dari ranah waktu ke ranah frekuensi memungkinkan ekstraksi parameter kritis seperti amplitudo, frekuensi dominan, dan pergeseran fase untuk setiap gelombang individu. Analisis ini menekankan kemampuan DFT dalam memetakan distribusi energi sinyal serta mengidentifikasi pola interaksi antarfrekuensi yang tidak teramati dalam domain waktu. Melalui simulasi numerik, ketepatan rekonstruksi sinyal berbasis komponen spektral dievaluasi dengan mempertimbangkan faktor seperti resolusi frekuensi dan efek aliasing. Hasil verifikasi menunjukkan bahwa DFT memberikan kerangka kerja yang andal untuk memahami dinamika superposisi gelombang, terutama dalam konteks pemrosesan sinyal real time.